KUALITAS PERAIRAN DI MUARA JANGARI – WADUK CIRATA - Garno, Yudhi Soetrisno (Jurnal Hidrosfir Indonesia, 2007)
It has been known that Jangari is an area in Cirata reservoir that could be developed as tourism area. Lately, in this area have been developing many cages for fish culture that produce organic waste in huge number and polute this area. This research was conducted to know the status and dynamic of water quality in Jangari that receive organic waste in huge number. This research concluded that Jangari water body could be cited as an eutrophic water body. This conclusion was due to (i). The concentrations of phosphorus was always higher than 0,016 mg·l-1P and nitrogen total was always higher than 0,711 mgxl-1N; (ii). The density of fitoplankton in 25 cm depth was between 36.590 x103 and 40.710x103 ind.l?1; whereas in 150 cm depth was between29.620 x103 and 36.370 x103 ind.l?1. This phytoplankton community was dominated by Cyanophyta (70,9%-78.2%); (iii). The vanishing point of secchi disc was always smaller than 71 cm. Although the community of phytoplankton was dominated by cyanophyta, especially Microcystis sp dan Oscillatoria sp that have been known as an unpalatable algae but the presence of zooplankton in the water body could be detected. During the research zooplankton was dominated by copepoda, cladosera and rotifera with density fluctuate between 34-394 ind.l?1.The eutrophic status for Jangari, will threaten the sustainable potency for tourism area; and therefore it was suggested to build one management for Cirata reservoir which could be hoped to plan, do and evaluate the development of Cirata appropriate to the potency and carryng capasity of reservoir.Keywords: Jangari, Organic waste, Phytoplankton, Eutrophic.